Pendidikan Islam Di Tengah Kemajuan Sains Dan Teknologi Moderen - Nurhilaliyah (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study aims to analyze the strategic role of Islamic education in responding to and directing the rapid development of modern science and technology (IPTEK). Although these advancements bring convenience and innovation, they also give rise to moral and ethical challenges due to the dominance of materialistic and secular paradigms. Islamic education functions as a guiding and supervisory force by emphasizing the values of tawhid and sharia as the primary standards for the development and utilization of science and technology. This research employs a qualitative-descriptive method through a literature review. The findings indicate that Islamic education must holistically integrate religious knowledge and general sciences through curriculum adjustments and improved learning methodologies. Key strategies include establishing Islamic creed (aqeedah) as the foundation for scientific and technological development, as well as positioning Islamic sharia as the ethical benchmark for its use. Furthermore, enhancing educators’ digital competencies and strengthening students’ digital literacy based on Islamic ethical principles are essential to mitigate the negative impacts of technology. In conclusion, Islamic education plays a vital role in shaping a generation of Muslim scholars who excel in science and technology while maintaining strong moral and religious values. Thus, science and technology can serve as instruments for achieving societal welfare and collective well-being.